Czy informatykom grozi bezrobocie? - Szewczyk, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article describes chances for taking up work in computer scientist profession. It also specifies sectors and trades, which computer scientists can count on fast employment. There are characterized the most desirable specialties by employers, too. The article includes the analysis of polls results, which concern the market of computer science professions in West Pomeranian province. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 448-462